Sampling and analysis of nickel, ferronickel and nickel alloys Part 5. Method for determination of by infra-red absorption after induction furnace combustion (BSI, 1986)
Nickel, Ferronickel, Ferro-alloys, Nickel alloys, Non-ferrous alloys, Determination of content, Carbon, Chemical analysis and testing, Gas analysis, Infrared radiation, Combustion test methods, Induction furnaces, Instrumental methods of analysis, Oxidation methods, Test equipment, Testing conditions, Safety measures, Calibration, Reproducibility, Crucibles (laboratory), Dimensions, Chemical composition, Volumetric analysis